L2 Chinese teachers' beliefs about engagement strategies for students in Australia: Findings from Q methodology research. (June 2022) - Yuan, Chengwen; Lo Bianco, Joseph
Abstract: In most Anglophone countries, the lack of engagement in the second language (L2) classroom has been recognised as one of the greatest challenges for L2 teachers, but there have not been many studies addressing teachers' beliefs about the issue. This study uses Q methodology to explore teachers' beliefs about engagement strategies held by teachers who teach Chinese as an L2 in Australian secondary schools. Twenty-five teachers with diverse backgrounds were recruited in this study, and they were asked to complete a Q-sort containing 48 statements related to engagement strategies. In the process, we identified four recurring clusters of beliefs as follows: orthodox subject-centred, progressive student-centred, nurturing effort-promoting and authoritative competition-encouraging. All teachers realise that following the structure of a given textbook closely and teaching to the test are not suitable approaches in Australia. However, they show different opinions about emphasising students' efforts, creating a fun learning environment and empowering students as partners in their learning. Implications for L2 Chinese teaching and teacher professional development in the Anglophone context are provided in this study.